(M)othering the Borderlands: Testimony and the Latina Feminist Group - Santos, Cristina; Crowe Morey, Tracy (Journal of the Motherhood Initiative for Research and Community Involvement, 2013)
With the publication of Gloria Anzaldúa’s Borderlands/La frontera (1987), women’s testimonial literature has been viewed as an important genre that breaks silences, raises consciousness and builds solidarity among women, especially Latinas and Chicanas. Testimonial writing functions as one means through which Latina/ Chicana writers, scholars, educators, and students are resisting traditional patriarchal conditions and constructs of motherhood to revise the institution as one based on empowerment through solidarity and sisterhood. In this paper, we explore the testimonial model established by the Latina Feminist Group as a vehicle through which to identify the diverse forms and contexts of mothering practices occurring at the borderlands of bi-geographical and bi-cultural identities. This paper is organized by way of four sections. The first provides an overview of Latin American and Chicana testimonial theory while the second section identifies testimonial writing as a pedagogy and site of diverse and multi-dimensional practices by Latina/Chicana mothers. For the final two divisions of the paper, we elaborate on the themes of solidarity and agency exemplified by the Latina Feminist Group as pedagogies for transformational (m)othering of the borderlands.